2015
DOI: 10.1371/journal.pone.0131504
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptome Analysis between Wild and Albino Yellow Catfish (Pelteobagrus fulvidraco)

Abstract: Body colours are important and striking features for individual survival and reproductive success, in particular in vertebrates where mating behaviour and mate preference may be strongly influenced by non-normal phenotypes. Pigmentation disorders may be generated by disruption of one or many independent genes as well as by environmental factors. The first discovery of albino yellow catfish (Pelteobagrus fulvidraco Richardson) with golden skin colour from fish farms in China provides us valuable material to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Based on the transcriptome analysis of T. fulvidraco (Zou et al ., ), partial cDNA sequences of tyr and tyrp1 were obtained. Then primer pairs (Tyr‐F and Tyr‐R; Tyrp1‐F and Tyrp1‐R) (Table ) were designed to amplify the Open reading frames (ORF) of both tyr and tyrp1 by the following PCR conditions: initial incubation at 95° C for 3 min, then 35 reaction cycles were run‐each consisting of 30 s at 95° C, 40 s at 57° C and 1 min 12 s at 72° C. The final step was conducted at 72° C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the transcriptome analysis of T. fulvidraco (Zou et al ., ), partial cDNA sequences of tyr and tyrp1 were obtained. Then primer pairs (Tyr‐F and Tyr‐R; Tyrp1‐F and Tyrp1‐R) (Table ) were designed to amplify the Open reading frames (ORF) of both tyr and tyrp1 by the following PCR conditions: initial incubation at 95° C for 3 min, then 35 reaction cycles were run‐each consisting of 30 s at 95° C, 40 s at 57° C and 1 min 12 s at 72° C. The final step was conducted at 72° C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that differentially expressed genes and mutations might contribute to this colour variation. Five colour genes, namely tyr , tyrp1 , slc7a11 , mreg and ednrb1a , were identified as differentially expressed genes, but no single‐base substitution mutations were found in colour‐related genes (Zou et al , ). To further investigate the regulation of colour related genes tyr and tyrp1 in wild and albino T. fulvidraco , full‐length complementary (c)DNA of these two genes were cloned, and the messenger (m)RNA expression levels were examined in various adult tissues and at different embryonic and larval development stages.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in albino rainbow trout Oncorhynchus mykiss , the associated phenotype is characterised by a white or yellow skin according to the species [ 4 ]. Albino yellow catfish Pelteobagrus fulvidraco have been observed in control breeding in China [ 5 ]. Albino individuals have also been observed among aquacultured Russian sturgeons, one of the most valuable freshwater fish species worldwide [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body colour and colour patterns are important phenotypic characters in most of the vertebrates, which help for mate selection, species recognition, crypsis and warning or threatening of predators in a living environment (Zou, Zhang, Shi, Lin, Ouyang, & Zhang, 2015). Changes in the colour pattern often lead to misidentification of an organism in a closely related species.…”
Section: Introductionmentioning
confidence: 99%